Subglottic stenosis and endobronchial disease in granulomatosis with polyangiitis. (14th June 2019) - Quinn, Kaitlin A; Gelbard, Alexander; Sibley, Cailin; Sirajuddin, Arlene; Ferrada, Marcela A; Chen, Marcus; Cuthbertson, David; Carette, Simon; Khalidi, Nader A; Koening, Curry L; Langford, Carol A; McAlear, Carol A; et al.
Abstract: Objectives: To describe tracheobronchial disease in patients with granulomatosis with polyangiitis (GPA) and evaluate the utility of dynamic expiratory CT to detect large-airway disease. Methods: Demographic and clinical features associated with the presence of subglottic stenosis (SGS) or endobronchial involvement were assessed in a multicentre, observational cohort of patients with GPA. A subset of patients with GPA from a single-centre cohort underwent dynamic chest CT to evaluate the airways. Results: Among 962 patients with GPA, SGS and endobronchial disease were identified in 95 (10%) and 59 (6%) patients, respectively. Patients with SGS were more likely to be female (72% vs 53%, P < 0.01), younger at time of diagnosis (36 vs 49 years, P < 0.01), and have saddle-nose deformities (28% vs 10%, P < 0.01), but were less likely to have renal involvement (39% vs 62%, P < 0.01). Patients with endobronchial disease were more likely to be PR3-ANCA positive (85% vs 66%, P < 0.01), with more ENT involvement (97% vs 77%, P < 0.01) and less renal involvement (42% vs 62%, P < 0.01). Disease activity in patients with large-airway disease was commonly isolated to the subglottis/upper airway (57%) or bronchi (32%). Seven of 23 patients screened by dynamic chest CT had large-airway pathology, including four patients with chronic, unexplained cough, discovered to have tracheobronchomalacia. Conclusion: SGS and endobronchial disease occur in 10% and 6% of patients with GPA, respectively, and may occur without disease activity in other organs. Dynamic expiratory chest CT is a potential non-invasive screening test for large-airway involvement in GPA.